PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU SD - Sukmaswati, Imas (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study is to describe (1) the role of school principals in improving the professional competence of elementary school teachers (2) the implementation of improvement in elementary teacher professional competencies and (3) efforts made by principals to improve the professionalism of elementary school teachers. This type of research is qualitative research. The data collection techniqueuses observation, interviews, and documentation. The results of the study show that (1) The role of school principals in improving teacher professional competencies in elementary schools is: a. Principal as educator b. Principal as manager c. Principal as supervisor (2) Implementation of teacher professional competency improvement in elementary school includes: a. master the material, structure, concepts, and scientific mindset that supports subjects b. master competency standards c. develop the learning material taught d. develop professionalism on an ongoing basis e. utilizing information and communication technology. (3) Efforts made by the principal in increasing the professionalism of teachers in elementary school through: a. By participating in the Teacher Working Group, b. Clinical supervision, c. Increased teacher work motivation and d. Fostering teacher performance.